Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1002/mds.28883
|View full text |Cite
|
Sign up to set email alerts
|

Discussion of Research Priorities for Gait Disorders in Parkinson's Disease

Abstract: A BS TRACT: Gait and balance abnormalities develop commonly in Parkinson's disease and are among the motor symptoms most disabling and refractory to dopaminergic or other treatments, including deep brain stimulation. Efforts to develop effective therapies are challenged by limited understanding of these complex disorders. There is a major need for novel and appropriately targeted research to expedite progress in this area. The Scientific Issues Committee of the International Parkinson and Movement Disorder Soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 108 publications
0
9
0
Order By: Relevance
“…It results from the loss of nerve cells in the basal ganglia, leading to the gradual decline of dopamine [3], [4]. The degeneration of dopamine-containing cells results in the deterioration of motor function and commonly causes gait disorders [5]. The diagnosis of PD is crucial to the development and improvement of treatment plans [6].…”
Section: Introductionmentioning
confidence: 99%
“…It results from the loss of nerve cells in the basal ganglia, leading to the gradual decline of dopamine [3], [4]. The degeneration of dopamine-containing cells results in the deterioration of motor function and commonly causes gait disorders [5]. The diagnosis of PD is crucial to the development and improvement of treatment plans [6].…”
Section: Introductionmentioning
confidence: 99%
“…While several studies assessed the role of subcortical nuclei 5,[8][9][10] in the pathophysiology of gait impairment in PD, recent findings have expanded beyond basal ganglia disfunctions 10,11 and suggested a primary role for the brain cortex 4,12 . Both functional and molecular imaging studies showed that deficits in the integration between frontal and sensorimotor areas might contribute to the disruption of gait automation and favor the development of gait impairments 4,12 . More recently, studies on cortical visual processing showed that gait impairment correlate with visual perceptual deficits, thus supporting a role for visuomotor processing in the pathophysiology of gait impairment in PD 4,12 .…”
Section: Introductionmentioning
confidence: 99%
“…These dysfunctions are the first intrinsic causes associated with falls and are closely related to cognitive impairment, often leading to restrictions in the patient's quality of life 2–4 . In addition, with disease progression, these dysfunctions are resistant to dopaminergic treatment and deep brain stimulation (DBS) 5,6 . Therefore, revealing the neurophysiological patterns underlying different motor statuses, including sitting, standing, walking, dual‐task walking, and freezing of gait, is essential for developing the optimized therapy.…”
Section: Introductionmentioning
confidence: 99%
“… 2 , 3 , 4 In addition, with disease progression, these dysfunctions are resistant to dopaminergic treatment and deep brain stimulation (DBS). 5 , 6 Therefore, revealing the neurophysiological patterns underlying different motor statuses, including sitting, standing, walking, dual‐task walking, and freezing of gait, is essential for developing the optimized therapy.…”
Section: Introductionmentioning
confidence: 99%